Structural Design and Experimental Verification of a Buckling-Restrained Braced Frame System - Lopez, Walterio A.; Gwie, David S.; Lauck, Thomas W.; Saunders, C. Mark (Engineering Journal, 2004)
To satisfy the seismic performance goals required by the owner, the structural engineer of record proposed to use Buckling-Restrained Braced Frames (BRBFs) as the seismic force resisting system of a new seven-story building. Because not all of the testing requirements found in the Recommended Provisions for Buckling-Restrained Braced Frames were met by the braces specific to this project, the structural engineer of record proposed conducting three frame subassemblage tests to validate their BRBF design. This article is a case study that describes a viable BRBF design methodology and the tests conducted to support it. This article summarizes some of the experimental results and discusses possible design implications of some of the experimental findings.